Separatist Rebellion of Albanian Students in Kosovo and Metohija in 1981 as the Beginning of the Socialist Yugoslavia Breakdown - Šuvaković, Uroš V.; Stevanović, Obrad M. (Sociološki pregled, 2019)
This paper highlights the socio-historical preconditions arising before the protests of Albanian students in Kosovo and Metohija in 1981, which turned into an open separatist rebellion. These preconditions had their roots in the views of the Comintern regarding the national question in Yugoslavia, as well as in the decisions of the KPJ (Communist Party of Yugoslavia) Dresden Congress. The future development of the events in the post-war socialist Yugoslavia, from time to time, actualized these decisions and attitudes, and the process of the development of Yugoslav community headed towards its dissolution. Based on a sociological analysis of the contents of literature and original documents that have now become available to the scientifc public, a conclusion is drawn that the rebellion of Albanian separatists in Kosovo and Metohija (K&M) in 1981 was only an introduction to the process of Yugoslavia breakdown. Although it was suppressed by means of an eﬀective engagement of the forces of the police and the Yugoslav People’s Army (YPA), in accordance with the orders of the federal leadership, it meant the beginning of a process that was unstoppable. A permanent destabilization of Yugoslavia and Serbia continued through activities of low-intensity (propaganda, subversion, later attempted murders, murders, terrorist acts) in Kosovo and Metohija, but over time, there grew a cooperation between Albanian separatists and the separatists in other Yugoslav republics who came to a conclusion that it was a convenient moment for presenting their own separatist demands.The role of students in the rebellion in Kosovo and Metohija was only initial and marionette in nature: the separatists correctly estimated that it would be more difcult to use force against students, than against an open revolt. When the organizers realized that the number of students willing to directly participate was insufcient, they began to enlarge the protests with high school students and workers, but even then the state reaction was adequate.
Keywords: chauvinism; Albanian separatism; student protests in 1981; Yugoslavia; Kosovo (K&M)